2006
DOI: 10.1073/pnas.0504337103
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide 3-kinase and Akt are essential for Sonic Hedgehog signaling

Abstract: Hedgehogs (Hhs) are key signaling regulators of stem cell maintenance and tissue patterning in embryos, and activating mutations in the pathway that increase Gli transcriptional activity are causal in a diversity of cancers. Here, we report that phosphoinositide 3-kinase (PI3-kinase)-dependent Akt activation is essential for Sonic Hedgehog (Shh) signaling in the specification of neuronal fates in chicken neural explants, chondrogenic differentiation of 10T1/2 cells, and Gli activation in NIH 3T3 cells. Stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
349
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 421 publications
(367 citation statements)
references
References 28 publications
13
349
1
4
Order By: Relevance
“…S166 and S186 are known to be phosphorylated by Akt, which activates the Mdm2-mediated degradation of p53 (22,23). Recently, it was reported that Smo activates phosphoinositide 3-kinase (PI3K) and Akt, both of which belong to an essential Shh signaling pathway (24). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S166 and S186 are known to be phosphorylated by Akt, which activates the Mdm2-mediated degradation of p53 (22,23). Recently, it was reported that Smo activates phosphoinositide 3-kinase (PI3K) and Akt, both of which belong to an essential Shh signaling pathway (24). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We reported that EGF also increases Shh mRNA levels in primary HSC [58]. Evidence that two different growth factors that activate AKT in HSC induce HSC expression of Shh is intriguing because insulin like growth factor (IGF)1 cooperates with Shh to activate AKT-dependent post-translational mechanisms that stabilize Gli2 in Hhresponsive C3H101/2 cells [59]. Thus, there is growing evidence that Hh signaling modulates growth factor actions (and vice versa) in Hh responsive cells.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty liver disease was accompanied by increased hepatic expression of both Sonic hedgehog (Shh) ligand ( Figure 2A) and several Hh target genes, including the Hh receptor, patched (Ptc, Figure 2B), Gli-2, an Hh-regulated transcription factor ( Figure 2C), 29 and Frizzled related peptide (Frp)-1, a soluble inhibitor of canonical Wnt signaling ( Figure 2D). 30 Interestingly, induction of Sonic hedgehog ligand and the Hh signaling components Ptc and Gli-2 was greater in EtOH-fed mice than HF controls, whereas EtOH consumption did not potentiate HF diet-associated increases in Frp-1.…”
Section: Hh Pathway Activation Occurs During Fatty Liver Damagementioning
confidence: 99%